2010
DOI: 10.1007/s13258-009-0888-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity among indigenous landraces from sesame (Sesamum indicum L.) core collection in China as revealed by SRAP and SSR markers

Abstract: The molecular genetic diversity of 404 indigenous landraces from sesame core collection in China were evaluated by 11 SRAP and 3 SSR markers, 175 fragments were generated, of which 126 were polymorphic with an average polymorphism rate of 72%. Jaccard's genetic similarity coefficients (GS=0.7130), Nei's gene diversity (h=0.2418) and Shannon's Information index (I=0.3847) were calculated, a dendrogram of the 404 landraces was made, landraces from various zones were distributed throughout the dendrogram, accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 15 publications
6
33
4
2
Order By: Relevance
“…Therefore, SSR markers would be one of the useful molecular markers in sesame genetic diversity analyses and in marker assisted breeding programs. Our study showed congruence with the previous studies by Surapaneni et al (2014) and Zhang et al (2010). Zhang et al (2010) reported that SSR markers are appropriate for evaluation of genetic diversities in sesame and also concluded that extensive genetic divergence existed among indigenous and exotic collections of sesame.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, SSR markers would be one of the useful molecular markers in sesame genetic diversity analyses and in marker assisted breeding programs. Our study showed congruence with the previous studies by Surapaneni et al (2014) and Zhang et al (2010). Zhang et al (2010) reported that SSR markers are appropriate for evaluation of genetic diversities in sesame and also concluded that extensive genetic divergence existed among indigenous and exotic collections of sesame.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed congruence with the previous studies by Surapaneni et al (2014) and Zhang et al (2010). Zhang et al (2010) reported that SSR markers are appropriate for evaluation of genetic diversities in sesame and also concluded that extensive genetic divergence existed among indigenous and exotic collections of sesame. Park et al (2013) reported that 41genotype-specific alleles were identified for 12 of 14 SSR markers.…”
Section: Discussionsupporting
confidence: 91%
“…Out of the 114 scorable fragments, 97 were polymorphic revealing 85.08% polymorphism across the 33 varieties studied (Table 2). In this study primers based on GA/AG and GT/TG dinucleotides core repeats generated good profiles, which seem to indicate that the more frequent microsatellite in Sesamae contains the repeated dinucleotides (AG/GA) n and (GT/TG) n. Our results are in accordance with the SSR analysis reported earlier [18]. Baydar [27] reported that the sesame varieties with non-branching character having higher yield advantages for mechanized cultivation, because of their uniform maturity in a short growing period.…”
Section: Resultssupporting
confidence: 92%
“…Several types of molecular markers have been developed and applied to sesame genotyping, such as random amplified polymorphic DNA (RAPD) [14] [15], simple sequence repeats (SSR) [16], inter-simple se-quence repeats (ISSR) [17], amplified fragment length polymorphism (AFLP) [18], sequence-related amplified polymorphisms (SRAP) [19] and expressed sequence tags-SSR (EST-SSR).…”
mentioning
confidence: 99%